The Chow form of the essential variety in computer vision. (May 2018) - Fløystad, Gunnar; Kileel, Joe; Ottaviani, Giorgio
Abstract: The Chow form of the essential variety in computer vision is calculated. Our derivation uses secant varieties, Ulrich sheaves and representation theory. Numerical experiments show that our formula can detect noisy point correspondences